Preparation and characterization of an ultrafast photoconductive switch - Pham, Thanh Trung; Daniela, Bayer (Journal of Technical Education Science, 2010)
The semiconductor photoconductive devices to generate picoseconds and sub-picoseconds electrical signals have been the subject of intense research for the last two decades. Primarily the fast-growing demand for ultrafast photo-switches and photodetectors are of interests. In this paper, the preparation and characterization of the ultrafast photoconductive switch for generation of short current pulses are mentioned, which will be applied in the characterization of components, such as fast field effect transistor, fast resonant tunneling diodes and the investigation of pulse propagation called waveguides Current pulses are generated by a low-temperature grown GaAs (LT-GaAs) photoconductive switch and then guided through a coplanar waveguide. The pulse length is directly calibrated using photocurrent autocorrelation. An ultra-fast response time (within less than 10 ps) to the sub THz electromagnetic field pulse is shown.